(untitled) (TRISANGAM INTERNATIONAL REFEREED JOURNAL, 2023)
Chapter: 1 Introduction: In Tagore’s short stories, Rabindranath identified the direction of the light of the woman who was close to Rabindranath or the touch of the enlightened woman in Rabindranath’s family at an early age. He clarified the role of women directly in the source of some story. Keeping this in mind, the research paper was divided into several parts. Chapter: 2 In his family the elder brother’s wofe or wife of Rabridra, Mrinalini comes and gets educated at home or school. He also saw Saraladevi going to work for the first time in Rabindranath’s family. Later, the female teacher is seen... Leela Majumdar is one of them. Educated women : Some aspects of this stage : A. little educated women in Rabindranath’s stories are seen in the Postmaster, Ekratri, Samapti, Haimanti, Payala Nombor. B. Highly Educated Women – The highly educated women in Rabindranath’s story attend college. Some of them have achieved great results. These stories are: Adhyapak, Patra o Patri, Namanju Golpo. C. The Educational Job – Three stories discussed in this episode: Aparichita, Progotisanhar, Ses Purosksr. Chapter: 3 Politics and Women - Women have participated in political activities in various ways in subjugated India. Niece Sarala Devi directly stepped into the arena of politics. Again Santiniketan former Mamata Dasgupta sheltered the anarchist. They have influenced the story. Breakdown of this episode- A. Supporter of a single protesting hero-in the story ’Megh O Raudra’. B. Women on behalf of Swadeshi – Women in the story of ’Rajtika’. C. The story of ’Badnam’ sheltered the revolutionaries. D. Amiya in ’Namanjur Golpo’ is directly related to politics. Chapter: 4 In Rabindr’s family female writer, editor was born. As Swarnakumari or Mejbouthakurani Gnanda got companionship, On the other hand, women writers have appeared in his stories in different ways. For example- A. Collectors of writing-’Khata’ s Uma has collected songs of Vaishnavi. B. Essay writing and women editor- In ’Nastanir’ Charu is also sitting in the role of editor. C. Poet and Storyteller - Nirjharini of ’Darpaharana’. D. Mrinal’s also a poet in ’Stir Patra’. But her creativity did not known in her husband’s house. Chapter: 5 Rabindranath saw the love of insects of Bela and Mira loved gardening. They are Rabindra’s daughter. Again, the Hindu and Muslim problem worried him. The stories of this episode can therefore be called a light example of humanity. The three stories are- A. In the life-saving of the pig Jayakali of ’Unrighteous entry’ is active. B. Prakriti Associates - Aunti of ’Balai’. C. Kamala in ’Musalmanir Golpo’’ saves life by marrying and converting Own and cousin’s daughter. Chapter: 6 Bengali Women in Science Contributors - Featured in Rabindranath’s three stories. Jagdish Chandra Bose’s wife Abala Bose was Rabindranath’s idol. Rabindra’s Biographer Prabhatkumar’s niece Katyayani’s husband was a chemical engineer and also a foundation of Jadavpur. Let’s look at the discounts of this life. A. Scientist becomes grandfather’s co-worker, ’Seskatha’’s Achira. B. Abhik’s engineering studies takes money from Biva in ’Ravibar’ story. C. The science laboratory keeper Sohini save the ’laboratory’. Chapter: 7 Conclusion: Enlightenment women’s in Rabindra’s family is imprinted in his story, life is illuminated in also by his story.